Status in classical Athens - Kamen, Deborah (Princeton University Press, 2017)
The chapters in this work explore Chattel slaves, privileged Chattel slaves, freedmen with conditional freedom, metics, privileged metics, disenfranchised citizens, naturalized citizens, and much more